Ionotropic Glutamate Receptors Trafficking in Health and Disease - Jeremy Henley (Frontiers Research Topics, 2017)
The knowledge about the properties and importance of ionotropic glutamate receptor trafficking is ever increasing. Importantly, the pace of the progress has been accelerated in recent years. Here, our contributors provide a) reviews on specific topics that present an up-to-date overview of the field, as well as b) original articles with the relevant new findings.